The motherhood penalty in cross-national perspective: the importance of work-family policies and cultural attitudes - Budig, Michelle; Misra, Joya; Böckman, Irene (Luxembourg, 2010)
"Mothers' employment and earnings partly depend on social policies and cultural norms supporting work-family balance. While policies regarding parental leave and childcare may assist families in combining work and care, are these policies related to the economic penalties for motherhood? Using original social policy data with micro data from the Luxembourg Income Study, we examine relationships between specific policies and the motherhood earnings penalty. We consider how penalties vary across 22 countries, and how particular social policies link to motherhood penalties. Using data from the ISSP, we also show motherhood penalties are smaller where cultural attitudes supporting maternal employment are stronger."